Pemanfaatan Limbah Ampas Kopi Sebagai Subtitusi Filler Pada Sifat Campuran Aspal HRS-WC Dengan Variasi Perendaman - Djalil, Sri Anggriany; Nurdin, Abdul Rahim; Yunus, Ahmad Yauri (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Hot Rolled Sheet or Thin Layer Asphalt Concrete is a graded gap mixture that uses fine coarse aggregate, fillers, and asphalt in a certain ratio which is compacted hotly. HRS has high durability. Filler functions as a filler for voids between aggregates, the fillers that are often used are cement and fly ash. In this study, the filler used was coffee grounds waste.The purpose of this study was to analyze the effect of adding coffee grounds waste to the properties of the HRS-WC mixture with immersion variation. This study used coffee grounds waste with the addition of 20%, 40%, 60%, 80% and 100%. Samples were made of 61 briquettes consisting of 21 characteristic briquettes and 40 variation briquettes. Some samples were not immersion and some were immersion for 3, 7 and 14 days. Sampling refers to the 2018 Bina Marga Specifications. Sample testing uses a Marshall Test. The test results show that the effect of adding 20% coffee grounds waste with 3-day immersion, the Stability, Flow, Density, Marshall Quotient, VIM, VMA, and VFB values are all within the 2018 Bina Marga Specifications.